Multi-morbidity and blood pressure control: Results of a cross-sectional study among school teachers in Kerala, India - G K Mini; Malu Mohan; P S Sarma; K R Thankappan (Wolters Kluwer Medknow Publications, 2021)
The patterns of concordant and discordant comorbidities of hypertension and their association with hypertension control were ascertained in this cross-sectional study. A total of 402 adults with hypertension were identified from the baseline survey of a randomized controlled trial for hypertension control among school teachers in Kerala. Chronic conditions were captured and categorized into concordant and discordant comorbidities. Nearly 57% of teachers with hypertension reported multimorbidity. Concordant morbidity was reported by 44% and discordant by 21% of participants. The odds of hypertension control was higher among those who reported at least one discordant morbidity (odds ratio [OR]: 2.76, 95% confidence interval [CI]:1.69-4.49) and those who reported at least one concordant morbidity (OR: 2.08, CI: 1.37-3.16), compared to their counterparts. Hypertension control was higher for those who reported any comorbidity (OR: 2.37, CI: 1.51-3.71) compared to those who did not report any. Well-designed large-scale mixed methods studies are required to thoroughly explore multimorbidity and its relationship with hypertension control in India.